Automation of in-situ RHEED analysis by LabView - Tan, San San. (2009)
Reflection High Energy Electron Diffraction (RHEED) is a real-time technique for monitoring the surface structure during the growth of epitaxial thin films. For the typical RHEED, a beam of electrons at energy usually between 8 to 20KeV is incident onto the surface of the substrate at a glancing angle of a few degree from a RHEED gun. At the surface, a scattering process causes some energy loss and the diffracted beams leaving the substrate will strike onto a phosphor screen forming the diffraction patterns. A CCD camera is then used to capture the diffracted patterns for data analysis. RHEED has been commonly use with atom deposition such as Laser Molecular Beam Epitaxy (LMBE) system due to its low incident angle that makes it surface sensitive. The automation in-situ RHEED analysis in LabVIEW provides information such as the intensity of the diffracted pattern and the distance between two adjacent high intensity. By monitoring the intensity oscillation, the user is able to monitor the growth mode, measure the deposition rate and thickness of the epitaxial thin films. In addition, the lattice variation during the film deposition also can be examined by quantitative analyze the spacing of diffraction pattern. In this report, the programmatical construction of the automation in-situ RHEED analysis will be covered step by step. Two experiments were carried out with this application and the observation of RHEED intensity oscillation and temperature depended lattice variation confirmed the validity of our program. A stepwise RHEED analysis was introduced as an additional function to further enhance this application. The stepwise RHEED analysis provides user flexibility in performing the application and will be covered in this report as well. A manual in appendix A, including the stepwise RHEED analysis, was written to guide the user in using the application. Various problems were encountered during the hardware and software development of this project. All these problems and their solutions will be discussed in this report. Some recommendation for future development of this project will be given as well in Chapter 7 of this report.